Transcranial Doppler ultrasonography in the detection of venous to arterial shunting in acute stroke and transient ischaemic attacks. Issue 5 (November 1996) - Yeung, M; Khan, K A; Shuaib, A
Abstract : OBJECTIVES: To prospectively evaluate the prevalence of venous to arterial shunting in patients with acute stroke and transient ischaemic attacks (TIAs) using transcranial Doppler ultrasonography (TCD) with saline contrast. METHODS: A consecutive series of patients with stroke or TIA underwent contrast TCD. Patients were subsequently divided into groups according to causative factors for stroke or TIA. The prevalence of right to left shunt was assessed within these groups. RESULTS: A total of 210 patients underwent contrast TCD. A right to left shunt was detected in 28.6% of patients (60 of 210). Among the patients with cryptogenic stroke or TIA, 37.1% (43 of 116) had a positive contrast TCD whereas only 18% (17 of 94) with another identifiable cause had a positive test (P = 0.0024). When age was used to further classify those patients with cryptogenic stroke, TCD was positive in 59.3% patients (16 of 27) of < or = 50 years of age versus 30.3% of patients (27 of 89) > 50 years of age (P = 0.0058). CONCLUSIONS: There was a significantly higher prevalence of venous to arterial shunting in patients with stroke or TIA of undetermined cause than in stroke patients with identifiable aetiologies, as detected by contrast TCD. The prevalence of a venous to arterial shunt was significantly higher in the younger group with cryptogenic stroke. Saline contrast TCD is a relatively non-invasive bedside procedure useful in the detection of venous to arterial shunting.